Detailed Study on Electronic Data Energy Consumption Monitoring System Based on the Construction of Internet of Things - Yu, Ruiling; Smail, Boussaadi; ER, Rakesh K.; Kumar, Khushmeet; Lal, Sujesh P. (Recent Advances in Electrical & Electronic Engineering, 2023)
Background: Buildings, in the traditional sense, are becoming increasingly incapable of meeting modern humans’ pursuit of high-quality living and working environments. With the increasing pace of urban development, modern buildings are becoming increasingly popular. Objective: We investigate an electronic data energy consumption monitoring system based on the construction of Internet of Things for the airport building. Aim: A model based on Dynamic Programming Genetic Algorithm (DPGA) is proposed to generate parameter and service models based on user scenarios. Methods: Two definitions are presented for the communication format between the middleware and the Wireless Sensor Network (WSN); the software and hardware functions of the nodes of the system's WSN are designed, and part of the node is implemented. Finally, the specific implementation of the application program interface and data interface between the modules of the middleware system are described considering the internal environment of a typical office building as an example. The deployment plan of system nodes in specific environments and the division of similar areas are discussed. Results: The platform can strictly monitor and manage energy-consuming equipment. Conclusion: The proposed model can be used to achieve reasonable distribution of energy consumption, energy saving, and humanised and automated energy consumption monitoring functions in the office areas of large office buildings in modern cities.
Keywords: node deployment